The Analysis of Outdoor Climate, Moist Air Enthalpy and their Relation to Cooling Energy Consumption in the Tropics - Rattanongphisat, Waraporn; Suwannakom, Anantachai (International Journal of Engineering and Technology, 2018)
The air conditioned auditorium classroom was monitored for energy consumption by a monitoring platform. One year collected data from energy consumption and indoor climate monitoring systems and outdoor climate data in Phitsanulok province, Thailand, where its climate classified as the tropics, was employed to determine their relation by regression analysis. The analysis of climate data showed that the outdoor temperature above 26 oC was accounted for 70% of the year this emphasizes on cooling requirement. Furthermore, the hourly cooling energy consumption ranged from 8.1 to 10.3 kWh for indoor air temperature between 20 oC and 32 oC. Â The higher outdoor temperature causes the greater cooling energy consumption. The correlation between outdoor temperature and cooling energy consumption with linear regression showed the correlation coefficient of 0.38 while the correlation between temperature difference and enthalpy difference of the outdoor and indoor found the correlation coefficient of 0.71. This pointed out that the outdoor tropical climate highly affected to the cooling energy demand.